2009
DOI: 10.2478/v10051-009-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria for Six Sigma Projects in Slovenian Manufacturing Companies

Abstract: Selection Criteria for Six Sigma Projects in Slovenian Manufacturing CompaniesResearches reveal that successful six sigma implementation is related to proper six sigma project prioritisation and selection. This research is limited to the selection of six sigma projects in some manufacturing companies in Slovenia. The purpose of this study is to identify what criteria are considered for prioritisation and selection of six sigma projects and how six sigma projects are selected. A research sample is limited by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
1
12
0
2
Order By: Relevance
“…Mexican manufacturing companies recent research has focussed on CSFs, for example, Bañuelas and Antony (2002) reviewed the literature, Kumar (2007) conducted a study of CSFs in Britain, Hilton et al (2008) in Australia, Gosnik and Vujica-Herzog (2010) in Slovenia, Chakrabarty and Tan (2012) in Singapore, and Schön (2006) in Sweden. Until now, even though a considerable amount of research into the implementation of SS has been conducted in North America, only a few studies have been done in Europe and Asia.…”
mentioning
confidence: 99%
“…Mexican manufacturing companies recent research has focussed on CSFs, for example, Bañuelas and Antony (2002) reviewed the literature, Kumar (2007) conducted a study of CSFs in Britain, Hilton et al (2008) in Australia, Gosnik and Vujica-Herzog (2010) in Slovenia, Chakrabarty and Tan (2012) in Singapore, and Schön (2006) in Sweden. Until now, even though a considerable amount of research into the implementation of SS has been conducted in North America, only a few studies have been done in Europe and Asia.…”
mentioning
confidence: 99%
“…Finally, there are several CSFs related to employees such as project management skills, SS training, and experience, acceptance of change, employee empowerment, and trained project leaders (e.g., green and black belt holders). As for the benefits of SS implementation, it is concluded that not all SS projects result in great benefits (Gosnik, D., & Vujica-Herzog, N., 2010). However, cultivating these CSFs maximizes the likelihood of a successful SS implementation.…”
Section: Discussionmentioning
confidence: 99%
“…En otro estudio efectuado en empresas de fabricación en Eslovenia, se obtuvieron datos sobre información general, experiencias con la metodología Seis Sigma, herramientas y técnicas de Seis Sigma que se utilizan y los factores críticos de éxito para la implementación de Seis Sigma. Realizado a través del envío de un cuestionario por correo electrónico a cien empresas de fabricación, 21 cuestionarios fueron devueltos totalmente terminados en tres meses con una tasa de respuesta de 21% (Gosnik, & Vujica-Herzog, 2010). De acuerdo con Gosnik, & Vujica-Herzog (2010), los datos recogidos en los cuestionarios fueron completados por Seis Sigma máster cinturones negros (MBB), cinturones negros (BB), cinturones verdes (GB) y cinturones amarillos (YB).…”
Section: Issn: 2007-4042unclassified
“…Realizado a través del envío de un cuestionario por correo electrónico a cien empresas de fabricación, 21 cuestionarios fueron devueltos totalmente terminados en tres meses con una tasa de respuesta de 21% (Gosnik, & Vujica-Herzog, 2010). De acuerdo con Gosnik, & Vujica-Herzog (2010), los datos recogidos en los cuestionarios fueron completados por Seis Sigma máster cinturones negros (MBB), cinturones negros (BB), cinturones verdes (GB) y cinturones amarillos (YB). En las compañías donde no hay una metodología Seis Sigma, los participantes fueron los gerentes de calidad que trabajan en el campo de la gestión de calidad en las mismas.…”
Section: Issn: 2007-4042unclassified